Authorial Presence in English Research Articles in Medicine Written by American and Indonesian Authors - Tsaqifa, Tsabita Intan; Hardjanto, Tofan Dwi (Universitas Gadjah Mada, 2024)
The present research attempts to investigate authorial presence in English research articles in medicine written by American and Indonesian authors. In doing so, the study first attempts to describe first-person pronouns used to express authorial presence. Secondly, the research aims to examine the discourse functions of first-person pronouns in the research articles. Data for the present research were taken from 20 English research articles in medicine, consisting of 10 articles published in CA: A Cancer Journal for Clinicians (Wiley) and 10 in Medical Journal of Indonesia. A corpus of 81,657 words was analyzed with the help of a concordance program, WordSmith Tools 5.0 (Scott, 2008), to identify the occurrences of first-person pronouns used in research articles. A qualitative analysis was also conducted to examine the discourse functions of each first-person pronoun using the classification proposed by Filimonova (2005) and Tang and John (1999). Hopefully, the present research findings could indicate the intention of authorial presence in academic writing, specifically in medical research articles. The findings also contribute to investigating the difference between American and Indonesian authors in presenting themselves in academic writing.